2021
DOI: 10.1101/2021.10.09.21264799
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diagnostic accuracy of point-of-care lung ultrasound for COVID-19: A systematic review and meta-analysis

Abstract: Background. Point-of-care (POC) lung ultrasound (LUS) is widely used in the emergency setting and there is an established evidence base across a range of respiratory diseases, including previous viral epidemics. The necessity for rapid testing combined with the limitations of other diagnostic tests has led to the proposal of various potential roles for LUS during the COVID-19 pandemic. This systematic review and meta-analysis focused specifically on the diagnostic accuracy of LUS in adult patients presenting w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…Earlier studies examining the diagnostic accuracy of LUS in COVID-19 patients have shown a high degree of variation. In a meta-analysis conducted by Matthies et al the sensitivity of LUS in adult patients with suspected COVID-19 ranged between 68 to 96 % and specificity between 21 to 91 % [1].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies examining the diagnostic accuracy of LUS in COVID-19 patients have shown a high degree of variation. In a meta-analysis conducted by Matthies et al the sensitivity of LUS in adult patients with suspected COVID-19 ranged between 68 to 96 % and specificity between 21 to 91 % [1].…”
Section: Discussionmentioning
confidence: 99%